On the problem of estimation of the number of cycles in two-dimensional quadratic systems from the viewpoint of nonlinear mechanics - Leonov, G. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
Two-dimensional quadratic systems are considered as a Liénard equation with certain special nonlinearities. Theorems on the existence or absence of cycles are given.